1980
DOI: 10.1073/pnas.77.8.4953
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of recruitment of ovarian follicles by suppression of the secondary surge of follicle-stimulating hormone with porcine follicular field.

Abstract: The increased serum concentration of follicle-stimulating hormone (FSH; follitropin) between proestrus and estrus in the rat has been hypothesized to recruit the follicles destined to During the afternoon of the day known as proestrus in the rat estrous cycle the two gonadotropic hormones, luteinizing hormone (LH; lutropin) and follicle-stimulating hormone (FSH; follitropin), surge between 1400 and 2000 hr (1,2). By midnight between proestrus and the next day, estrus, the serum LH level returns to baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…(Bast & Greenwald, 1974). Beginning at 22:00 h on Day 4, there is an increase in serum FSH, accompanied by low levels of LH, which is sustained throughout the afternoon of Day 1 (Siegel, Bast & Greenwald, 1976 (Peluso & Steger, 1978) and causes follicular recruitment in the rat (Hoak & Schwartz, 1980) and in the hamster (Greenwald, 1975;Greenwald & Siegel, 1982). Eshkol & Pariente (1984) have shown that FSH significantly stimulates [3H]thymidine incorporation in rat granulosa cells in culture while hCG has no effect.…”
Section: Isolation Offolliclesmentioning
confidence: 99%
“…(Bast & Greenwald, 1974). Beginning at 22:00 h on Day 4, there is an increase in serum FSH, accompanied by low levels of LH, which is sustained throughout the afternoon of Day 1 (Siegel, Bast & Greenwald, 1976 (Peluso & Steger, 1978) and causes follicular recruitment in the rat (Hoak & Schwartz, 1980) and in the hamster (Greenwald, 1975;Greenwald & Siegel, 1982). Eshkol & Pariente (1984) have shown that FSH significantly stimulates [3H]thymidine incorporation in rat granulosa cells in culture while hCG has no effect.…”
Section: Isolation Offolliclesmentioning
confidence: 99%
“…The physiological significance of high FSH levels and FSHR gene expression during oocyte maturation and spawning in salmonids remains puzzling. However, in mammals (Hoak & Schwartz 1980) and fish (Prat et al 1996, Tyler et al 1997, it has been proposed that FSH plays a role in follicle recruitment for the next reproductive cycle. Meanwhile, recombinant FSH injected into female rats induces not only follicle growth but also ovulation (van Cappellen et al 1995).…”
Section: Expression Of the Gth Receptor Genes In The Gonadmentioning
confidence: 99%
“…Although there are fewer data in mice, the pattern of FSH release across their estrous cycles appears to be very similar (Nequin et al 1979, Tejada et al 1998, Ahn et al 2004. Whereas the primary FSH surge has limited or no functional relevance (DePaolo et al 1979, Hoffmann et al 1979, the secondary surge is fundamentally required for persistent cycles of ovarian follicle selection and maturation (DePaolo et al 1979, Hoak & Schwartz 1980. Given their relative physiological importance, it is noteworthy that the primary surge in rats depletes intra-pituitary FSH stores (Ortolano et al 1988, Chapman & Woodruff 2003.…”
Section: Introductionmentioning
confidence: 99%